Significant usage of slab and wall form technique in IBS for low cost high rise apartment's construction / Marziah Rosli - Rosli, Marziah (2008)
In Malaysia, there are many construction method available practices. Most of the methods claim they are the best to be used. However, some of the method fails to show that their method best in cost and quality. In this Final Project report, comparison will be done to various method of construction to find which is the most efficient and effective. The results that were obtained through these experiments showed that the proposed method solution is highly accurate.